Personal Narratives: A Pedagogical Proposal to Stimulate Language Students' Writing - Fredy Orlando Salamanca González (Asociación Colombiana de Profesores de Ingles, 2015)
In a public university in Tunja (Colombia), undergraduate language students mentioned that writing was important and yet, they kept at a distance from it due to its requirements. The aim of this pedagogical intervention was to find a strategy to encourage students to write and, more importantly, to feel an identity with their texts. For this pedagogical intervention, students were required to write narratives that allowed them to portray their experiences using the target language and to look for the most accurate words and descriptions. From a pedagogical perspective, writing the narratives provided the teacher with the possibility of knowing his students better and to feel an affiliation towards them.